Traditional Rights of Indigenous People in Indonesia: Legal Recognition and Court Interpretation - Sartika Intaning Pradhani (Jambe Law Journal, 2018)
Indigenous peoples are victims of agrarian conflict, but their existence are not recognized by Indonesia. Indonesia recognizes Adat Law Community, distinct community living in Indonesia according to their Adat Law, and their traditional right. This paper is written based on legal normative research to analyze right of Adat Law Community towards their land and territory; and rule of the court regarding right of Adat Law Community. Adat Law Community has strong relation with their land and territory, namely Ulayat Right which guaranteed in Constitution and regulated in various law and regulation, especially regarding natural resources. Recognition towards Ulayat Right held by Adat Law Community through regional law product is declaratory because it only confirms the exiting right. Court has prominent role to enforce right of Adat Law Community. Constitutional Court has revoked several provisions in law which neglect Ulayat Right of Adat Law Community, such as Adat Forest which defined as state forest located in Adat Law Community’s territory; and Right of Coastal Water which limits Ulayat Right of Adat Law Community to access natural resources in coastal area and small islands. Though Constitutional Court has strengthen right of Adat Law Community, this community still face difficulties to claim their right towards land and territory against government and investor before District Court, High Court, and Supreme Court because those Court more focus on formal legal certainty of Adat Law Community’s authorization towards their land and territory than factual authorization as narrated by the community.